Fenomenenalni ! razvoj tekmovalne kariere Petra Prevca - Jošt, Bojan (Šport (Ljubljana), 2016)
Peter Prevc's podium positions, medals and victories at top-level ski jumping competitions have grown from year to year over the last seven seasons. Among all the counting and statistical processing, one cannot ignore the simple fact that Prevc is an outstanding athlete who, at the age of 23, can be ranked along side the greatest ski jumping champions. In the last 2015/2016 season, Prevc actually achieved everything that is possible. There are no big and small ski jumps for him. He can win and set records anywhere, at any moment, in any place; in fact, it all depends on his inspiration and the competition circumstances. Peter Prevc's fame has been growing and developing in Slovenia and internationally; he has quickly gained broad recognition in the media and in social arenas. Everybody, young or old, speaks about him with great respect and in mythical tones. Has this young ski jumping champion been attributed with some divine properties, serving as a role model for many young athletes and non-sportspeople all over the world? Many today are wondering what are the reasons for his top competitive performance. In professional terms, this unbelievable development of Peter Prevc's competitive career also raises many other questions.
Keywords: Prevc, Peter; ski jumps; slovenski športniki; smučarski skoki; sport; šport; top achievements; vrhunski dosežki